POTENSI KETERSEDIAN AIR TANAH DAN NERACA AIR WILAYAH KARST DI KABUPATEN MAROS: Potential Availability of Groundwater and Water Balance of Karst Area in Maros Regency - Muh Abbas; Burhanuddin Rasyid; Mahmud Achmad (Universitas Hasanuddin, 2022)
Water balance calculations can describe water conditions in an area. Climatic conditions and soil characteristics will affect the water balance in an area, including the karst areas which is vulnerable to droughts. This study analyzes the capacity of the soil to store water and calculates the regional water balance. By using the Soil Moisture Equipment Corp at a pressure of 0.33 atm, the field capacity of the soil and a pressure of 15 atm will be known to obtain the permanent wilting point value. The regional water balance was calculated using the Thornthwaite-Mather method. Research conducted in the karst area of ​​Maros Regency shows that the available water pore value with very low criteria so that it affects the available water capacity. The water balance of the karst region shows a surplus in November-June and a deficit in July-October. The total value of surplus is 1296 mm/year and deficit is 370 mm/year.